Diversity of Human Milk Oligosaccharides and Effects on Early Life Immune Development - Ayechu-Muruzabal, Veronica; van Stigt, Arthur H.; Mank, Marko; Willemsen, Linette E. M.; Stahl, Bernd; Garssen, Johan; van't Land, Belinda (Frontiers in Pediatrics, 2018)
One of the well-known features of human milk, is the capacity to protect against the risk and impact of neonatal infections, as well as to influence the onset of allergic and metabolic disease manifestations. The major objective of this review is to provide a detailed overview regarding the role of human milk, more specifically the diversity in human milk oligosaccharides (HMOS), on early life immune development. Novel insights in immune modulatory effects of HMOS obtained by in vitro as well as in vivo studies, adds to the understanding on how early life nutrition may impact immune development. Extensive description and analysis of single HMOS contributing to the diversity within the composition provided during breastfeeding will be discussed with specific emphasis on immune development and the susceptibility to neonatal and childhood infections.